Pakistan - Balochistan Economic Report : From Periphery to Core, Volume 1. Summary Report - World Bank (Washington, DC, 2012)
Balochistan offers some of the best assets for development. Balochistan is generously bestowed with natural and locational resources. It possesses the largest land area of any province of Pakistan, proving vast rangeland for goats, sheep, buffaloes, cattle, camels and other livestock. Its southern border makes up about two thirds of the national coastline, giving access to a large pool of fishery resources. As a frontier province, it is ideally situated for trade with Iran, Afghanistan, Central Asia and the Persian Gulf countries. Over the last four decades, it supplied cheap natural gas to Pakistan's economic centers, supporting the country's industrialization. This report offers an empirical analysis of provincial economic development and the ways in which the provincial and federal governments, supported by donors, can help to foster it. It is organized around three topics: the stock taking of economic outcomes over the last decades; the Strategies for inclusive economic development of generating growth, delivering services, and financing development in the future; and the instruments for today's economic policies to bring about the required changes. The five main findings of the report are as follows. First, there are good reasons to be optimistic about Balochistan's development. Provincial and federal reforms, the synergies between Balochistan's and Pakistan's development agenda in the areas of energy and trade, and the strong performance of the national economy present a unique opportunity to move Balochistan from the periphery to the core of economic development to the benefit of its people. Second, in order to overcome the challenges that held back provincial development for many decades, Balochistan should pursue a development agenda around generating growth, delivering services, and financing development. This approach can make sure that Balochistan's development path is inclusive, where the gains are shared across regions and population groups. Third, generating growth requires leveraging Balochistan's resource and locational advantages, deepening its capacity for value-addition, and strengthening the foundations for business activity. Fourth, delivering services depends on improving the public administration, making devolution more effective and scaling-up of basic services with innovative approaches involving the private sector and communities. Finally, financing development relies on a prudent management of provincial expenditures, strengthening the capacity for revenue collection, and advancing fiscal devolution.